Ksharkarmaas A Management of Charmakeela(Warts) – A Review: Life Sciences-Medicine - Singh, Dr. Naveen; Dasar, Dr. Devyani; Gv, Dr. PavithraJaivarshaa; Kumar, Dr. Akshay; Abhishek, Dr. (International Journal of Life Science and Pharma Research, 2023)
Anything resembling a nail or bound to the skin is called charmakeela in Ayurveda. Charmakeela is a condition that hasexisted since ancient times and requires more attention for cosmetic reasons. Acharya Sushrutha mentions Charmakeela as akshudraroga. The pathogenesis of this disease is caused by vitiation of vyanavata and kapha over the skin, resulting in the formationof a hard, hard nail-like structure known as Charmakeela. They exhibit different characteristics depending on the dominant dosha.Vata dominant Charmakila (Warts) are ruksha and ruja; Pitta dominant Charmakila (Warts) are Krishna varna; and Kapha dominantCharmakila (Warts) are kwacha varna, snigdha, and granthi. Sushruta Samhita, AstangaHridaya, MadhavNidana, Yogratnakara, andBhavapraksha all mention Charamkeela. Based on the signs and symptoms described in the classics, Charmakeelacan be comparedto Warts. Warts, also known as verrucae, are a common skin condition caused by the Human Papillomavirus (HPV). Sushruthamentioned Charmakeela while describing the indication of KsharKar main SushruthaSamhitha. Kshara is composed of several drugsin their most concentrated and subtle forms; it has kshanana and shodana propertiesand uses tikshnaguna, which aids in the externaldesquamation of warts. Because of their cleansing and antiseptic properties, Ksharaaids in the Ropana (healing process). The aimis Ksharkarma as a management of Charmakeela(Warts) – A Review. Material collected from many Ayurvedic texts, such as theSamhita, online resources, journal papers, and books, are available. It can be concluded that Kshar Karma is an effectiveayurvedictreatment forcharmakeelathat has no side effects. Because it does not leave scars or cause recurrence, this non-invasive indigenoustherapeutic technique is more effective in treating Charmakeela.